Marine microbes and plastic debris research status and opportunities in the Philippines [Review article] - Onda, Deo Florence L.; Viernes, Alvin Claine A.; Perez, Jose Nickolo O.; Calpito, Jahannah Victoria M.; Bitalac, Justine Marey S.; Tolentino, Mark Paulo S.; Purganan, Daniel John E.; Gomez, Norchel Corcia F. (2020)
Marine plastics have been shown to affect all organisms across the trophic levels including the microbial communities, influencing their community assembly, composition, metabolic processes, and ecosystem functions. Thus, studying plastic-microbe interactions in the marine environment is important in understanding its implications alongside the growing issue of plastic pollution. The Philippines, despite being suggested as the third-largest contributor to marine plastic debris, currently does not have any existing national research programs on basic plastics research, resulting in our limited understanding of the extent and implications in the country. This paper then reviews the current status and knowledge of the plastic-microbe association focusing on how plastic surfaces serve as a new environment for marine microbes, how this system could become dispersal mechanisms of unwanted microorganisms, and how microbes possibly contribute to the biodegradation of plastics in the marine environment. These also translate to possible research opportunities for Filipino scientists to work on the topic. (Author's abstract)